Pengaruh Harga Tiket, Promosi, dan Fasilitas Bioskop terhadap Keputusan Menonton di CGV Grand Batam - Nurul Hidayati; Septa Diana Nabella; Muhammad Rahmat (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study analyzes the influence of Ticket Prices, Promotion ), and Cinema Facilities on Watching Decisions at CGV Grand Batam. Using a quantitative associative design, a sample of 100 respondents was selected from a population of 294,516 using the Slovin formula (10% margin of error). Data were collected via questionnaires and analyzed through multiple linear regression.The F-test results show that all variables simultaneously have a significant effect on watching decisions (F-count 15.911; sig. 0.001 < 0.05). Partially, the t-test results confirm that each independent variable significantly impacts the dependent variable: Ticket Prices (t = 6.016), Promotion (t = 6.127), and Cinema Facilities (t = 5.885), all with significance values below 0.05. These findings indicate that competitive pricing, attractive promotions, and comfortable facilities are key drivers of consumer behavior. Accordingly, CGV Grand Batam is suggested to maintain its pricing strategy, optimize promotional activities, and continuously enhance facilities to sustainably increase consumers’ watching decisions.